Cervicovaginal Microbiota Predicts Neisseria gonorrhoeae Clinical Presentation - Lovett, Angela; Seña, Arlene C.; Macintyre, Andrew N.; Sempowski, Gregory D.; Duncan, Joseph A.; Waltmann, Andreea (Frontiers in Microbiology, 2022)
Neisseria gonorrhoeae infection of the female lower genital tract can present with a spectrum of phenotypes ranging from asymptomatic carriage to symptomatic cervical inflammation, or cervicitis. The factors that contribute to the development of asymptomatic or symptomatic infections are largely uncharacterized. We conducted a pilot study to assess differences in the cervicovaginal microbial community of patients presenting with symptomatic vs. asymptomatic N. gonorrhoeae infections to a sexually transmitted infections (STI) clinic. DNA was isolated from cervicovaginal swab specimens from women who tested positive for N. gonorrhoeae infection using a clinical diagnostic nucleic acid amplification test. We performed deep sequencing of 16S ribosomal RNA gene amplicons, followed by microbiome analyses with QIIME, and species-specific real-time PCR to assess the composition of microbial communities cohabitating the lower genital tract with the infecting N. gonorrhoeae. Specimens collected from asymptomatic individuals with N. gonorrhoeae infection and no co-infection with Chlamydia trachomatis and/or Trichomonas vaginalis carried Lactobacillus-dominant microbial communities more frequently than symptomatic patients without co-infection. When compared to asymptomatic individuals, symptomatic women had microbial communities characterized by more diverse and heterogenous bacterial taxa, typically associated with bacterial vaginosis (BV) (Prevotella, Sneathia, Mycoplasma hominis and Bacterial Vaginosis-Associated Bacterium-1 (BVAB1)/”Candidatus Lachnocurva vaginae). Both symptomatic and asymptomatic N. gonorrhoeae patients with additional STI co-infection displayed a BV-like microbial community. These findings suggest that Lactobacillus-dominant vaginal microbial community may protect individuals from developing symptoms during lower genital tract infection with N. gonorrhoeae.